Effects of 1% Topical Brinzolamide on Intraocular Pressure in Healthy Dogs - Dower, Nathalie Moro Bassil; Maciel, Camila do Espirito Santo; Spiller, Paulo Roberto; Pizzinatto, Fábio Dumit; Gomes, Lianna Ghisi; Yamauchi, Kelly Cristiane Ito; Gonçalves, Lucas Alaião; Pinheiro, Alexandre Pinto (Acta Scientiae Veterinariae, 2016)
Background: Glaucoma is one of the most common causes of blindness in dogs, and is generally characterized by death of the retinal ganglion cells associated with a rapid loss of vision. Increased intraocular pressure (IOP) occurs in patients with primary glaucoma, due to genetic abnormalities in pectinal ligaments and the trabeculae of the iridocorneal angle, producing inadequate drainage of aqueous humor. IOP is the result of the dynamic equilibrium between the production and drainage of aqueous humor. Intraocular surgery, anterior lens luxation, systemic diseases, immune-mediated, neoplastic and infectious diseases lead to the breakdown of the blood-aqueous barrier and increase the amount of protein and cells in aqueous humor, which can block this drainage pathway. Under these conditions, becomes indispensable the pharmacological control of IOP by reducing aqueous humor production. The main objective of the present study was to evaluate the effects of topical 1% brinzolamide on intraocular pressure (IOP) in twelve healthy dogs. Materials, Methods & Results: The age range of affected dogs was 1-5 years, with a mean age of 2.5 years. Twelve dogs were included in this study. All animals were healthy based on clinical, ophthalmic and hematological examinations. Selected animals were kept in a room with 500 lux luminosity, 56.8% relative humidity, 20°C temperature, exposed to 12 h of light/dark cycle, were fed twice daily and water ad libitum. All animals were adaptation to the procedures and examiners and IOP was measured by applanation tonometry at 08:00 a.m., 11:00 a.m., 02:00 p.m., 05:00 p.m., and 08:00 p.m., for 7 days and 2 days of baseline. Subsequently, one eye of each dog was randomly assigned, the eye received one drop of 1% brinzolamide at 08:30 a.m., 02:30 p.m., and 08:30 p.m. during four consecutive days and adelfo eyes received one drop of sterile saline solution and were considered control eyes. During the treatment phase and on the day after the treatment had finished, all parameters were evaluated in a blind fashion at the same pre-established time points. The value for IOP during the baseline of the treated eye were 16.77 ± 0.22 mmHg. The baseline period, values did not differ significantly between treated and control eyes. Comparison between the first day of brinzolamide-treated eyes with the average daily values of the two days of the baseline period showed that IOP decreased significantly 8.88%. IOP after four days of daily instillations of brinzolamide was able to decrease overall IOP by 1.42 mmHg (8.47%) when compared with the baseline period. Overall IOP values in the brinzolamide-treated eyes decreased 1.02 mmHg (6.24%) when compared to the control eyes. There were no statistically significant differences when compared control eye to baseline. Three times daily instillations of 1% brinzolamide in healthy dogs significantly decrease 8.47% IOP. During the post-treatment period, the average daily values of the brinzolamide-treated eyes remained 1.52 mmHg below the average daily values observed at baseline period. Discussion: The present research showed that, the average daily IOP values in the brinzolamide-treated eyes decreased 1.49 mmHg (8.88%) at the end of the first day, 1.69 mmHg (10.07%) at the end of the fourth day, and the cumulative IOP values after four days of treatment, were able to decrease by 1.42 mmHg (8.53%). Three times daily instillations of 1% brinzolamide in healthy dogs significantly decrease IOP, and therefore may be indicated to management of intraocular hypertension and glaucoma.